Blue grouse : their biology and natural history - Zwickel, F. C. (NRC Research Press, 2004)
This monograph is about blue grouse (Dendragapus obscurus). Designed as a reference work, it documents and reviews much of what is known about the biology and natural history of this bird. It is based primarily on our published and unpublished long-term studies in British Columbia and elsewhere, and on the studies of others in various parts of the bird's range.